Maintaining the firmness of minimally processed papaya using pectin methylesterase and calcium lactate (Research, Society and Development, 2020)
The objective of this work was to evaluate the effect of vacuum infusion of pectin methylesterase (PME) and calcium lactate (C6H10CaO6) in maintaining the firmness of minimally processed papaya, in order to maintain the quality and cellular integrity of the fruit. After minimal processing, the treatments used were: fruit without infusion (control), with H2O infusion, with PME infusion, with C6H10CaO6 infusion and with PME+C6H10CaO6 infusion. At zero times, four and eight days of storage, analyzes of total galacturonic acid, methanol, cell integrity, vitamin C, pH, acidity, soluble solids, damage, freshness and contamination were performed. Papaya treated with the PME+calcium combination showed an increase in firmness (5.8 N) on the eighth day of storage, differing from the control treatment (1.3 N), reporting the least leakage of electrolytes. On the fourth day, the fruit treated with PME+C6H10CaO6 showed the highest content of galacturonic acid and on the eighth day the highest content of methanol, indicating an effective action of the enzyme PME and calcium in this period. The PME+C6H10CaO6 treatment was effective in maintaining and improving the quality of papaya while preserving freshness, soluble solids content, acidity and pH throughout storage.